Two-component fast curing adhesive

By introducing phosphoric acid and/or phosphate esters into epoxy resin and acidic phosphorus-containing two-component adhesives, combined with calcium carbonate, minerals and other components, the peel resistance and resistance of epoxy adhesives in the prior art are solved and The problem of insufficient adhesion achieves high-performance bonding effect on a variety of substrates.

CN119213067APending Publication Date: 2024-12-27ZEPHYROS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380036203.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-25
Filing Date
2023-04-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing rapid curing epoxy adhesives have shortcomings in terms of peel resistance and adhesion, especially in the case of bending, peeling and off-axis loads, and their performance on different substrates is inconsistent, which limits their performance in Applications in manufacturing and repair.

Method used

A two-component adhesive system containing an epoxy resin and an acidic phosphorus-containing component is used, wherein the phosphoric acid and/or phosphate esters are reacted with the epoxy resin as the main activator to form an adhesive with improved T peel resistance and adhesion. Mixtures, including components such as calcium carbonate, minerals, reinforced fibers and hydrophobic silica.

Benefits of technology

Improved peel resistance and adhesion on various substrates is achieved, providing a T peel strength of at least 2.5N/mm and a overlap shear strength of 15MPa. It is suitable for a variety of substrates, including polluting the environment, and improving The overall performance of the adhesive is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100326120000101
    Figure BDA0005100326120000101
  • Figure BDA0005100326120000111
    Figure BDA0005100326120000111
  • Figure BDA0005100326120000261
    Figure BDA0005100326120000261
Patent Text Reader

Abstract

The present teachings provide an adhesive formulation comprising a moiety A having an epoxy resin and a moiety B having an acidic phosphorus-containing component, wherein the adhesive has a T peel of at least about 2.5 N / mm as measured according to ASTM D1876.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present teachings generally relate to fast-curing, room-temperature-curing, two-component adhesives that contain some epoxy functionality while providing improved T-peel resistance and adhesion to a range of substrates. The present invention employs phosphoric acid and / or phosphate esters and / or other acidic components as the primary activator and curing agent to react with a mixture containing epoxy-functional materials as the primary co-reactant. Background Art

[0002] Fast setting epoxy adhesives, including the class of products known as 5-minute epoxies, are well known in the commercial industry. Typically, they cure quickly but are not considered to have an attractive set of aggregate properties. To date, there has been a significant trade-off between fast reaction time and reduced physical properties and less durable adhesion to a variety of substrates. Various curing agents, hardeners, or activators have been used to manufacture these adhesives, which are commonly found in hardware stores and DIY centers. Although the adhesives can have high shear strength, their use as assembly adhesives in manufacturing and durable repair solutions is limited due to their lack of peel resistance, a common method of evaluation being the T-peel test. This lack of peel resistance limits their use in applications where bending, peeling, and off-axis loads may be important factors. In addition, the quality of adhesion often varies across a range of substrates, with inconsistent lap shear strength for each type of substrate being one manifestation of this phenomenon.

[0003] Despite the above teachings, there remains a need for fast curing adhesives having an appropriate blend of particulate toughening agents and flexibilizers such that the immiscible elastomeric toughening phase is properly blended with sufficient matrix plasticization to improve physical characteristics.

[0004] The present teachings provide one or more of the above benefits. The adhesive materials of the present teachings can be used to provide fast curing adhesives having one or more of improved peel resistance, improved lap shear, and improved adhesion on a variety of substrates, including when contaminants are present. Summary of the invention

[0005] The present teachings provide an adhesive comprising a part A having an epoxy resin and a part B having an acidic phosphorus-containing component. The cured adhesive has a T-peel of at least about 2.5 N / mm as measured according to ASTM D 1876.

[0006] The teachings herein further relate to a curable adhesive formulation comprising a part A having one or more epoxy resins and a part B having an acidic phosphorus-containing component. The adhesive comprises one or more of calcium carbonate, minerals, reinforcing fibers, hydrophobic silica, or any combination thereof.

[0007] The teachings herein further relate to a curable adhesive formulation comprising a part A having one or more epoxy resins and a part B having an acidic phosphorus-containing component. The cured adhesive has a T-peel of at least about 2.5 N / mm as measured according to ASTM D1876.

[0008] The cured adhesive may provide an assembly having a lap shear of at least about 15 MPa as measured in accordance with EN 2243-1.

[0009] The acidic phosphorus-containing component may include one or more phosphate esters, phosphoric acid, polyphosphoric acid, phosphorus pentoxide, or any combination thereof. The one or more phosphate esters may include a first phosphate ester, a second phosphate ester, a third phosphate ester, or any combination thereof.

[0010] The one or more phosphate esters can be, independently of one another, reaction products of phosphoric acid with: an alcohol; an epoxy group of a phosphate ester precursor (i.e., a component that has not yet reacted with phosphoric acid); a monoepoxy-functional molecule; a glycidyl ether of cashew nut shell liquid (CNSL) diphenyl glycidyl ether; 2-ethylhexyl glycidyl ether; and / or epoxidized p-tert-butylphenol.

[0011] The one or more phosphates may be present in an amount of about 0.1% to about 30% by weight of the B side; preferably about 10% to about 14% by weight of the B side. The at least one phosphate may be present in an amount of about 10% to about 60% by weight of the B side; preferably about 25% to about 35% by weight of the B side; more preferably about 28% to about 32% by weight of the B side. The at least one phosphate may be present in an amount of about 5% to about 40% by weight of the B side; preferably about 15% to about 25% by weight of the B side; more preferably about 18% to about 22% by weight of the B side. The at least one phosphate may be present in an amount of about 10% to about 65% by weight of the B side; preferably about 35% to about 45% by weight of the B side.

[0012] Part B may include one or more non-phosphorus-containing acids or derivatives, one or more anhydrides, one or more additives, one or more monomers, or any combination thereof.

[0013] The one or more additives may include minerals, reinforcing fibers, fumed silica, or any combination thereof. The adhesive may include calcium carbonate. The adhesive may include an elastomeric material. The adhesive may include one or more of calcium carbonate, minerals, reinforcing fibers, hydrophobic silica, or any combination thereof.

[0014] The two-part system may include calcium carbonate present in an amount of about 1 wt % to about 25 wt % of Part A; preferably about 4 wt % to about 18 wt % of the A side; more preferably about 8 wt % to about 12 wt % of the A side.

[0015] The two-part system may include a core-shell material.The two-part system may include hydrophobic silica.The two-part system may include platy alumina.

[0016] The one or more epoxy resins may include one or more liquid epoxy resins, one or more flexible epoxy resins, one or more epoxy phenolnovolac resins, one or more aliphatic multifunctional epoxy resins, one or more reactive diluents, one or more silane-modified epoxy resins, or any combination thereof.

[0017] An adhesive according to any one of the preceding claims, wherein the one or more epoxy resins comprise one or more liquid epoxy resins.

[0018] The adhesive of claim 21, wherein the one or more liquid epoxy resins are independently the reaction product of epichlorohydrin and: a bisphenol; preferably bisphenol A, bisphenol F or both.

[0019] The one or more liquid epoxy resins may have: an epoxy equivalent weight of about 100 g / equivalent to about 1000 g / equivalent as measured according to ASTM D 1652-97; an epoxy percentage of about 20 to about 25; and / or a viscosity of about 10 cP to about 100,000 cP at 25° C. as measured according to ASTM D445. The one or more liquid epoxy resins may be present in an amount of about 4 wt % to about 50 wt % of the A side. The one or more liquid epoxy resins may be present in an amount of about 10 wt % to about 30 wt % of the A side. The one or more liquid epoxy resins may be present in an amount of about 8 wt % of the A side.

[0020] The one or more epoxy resins may include one or more flexible epoxy resins; preferably independently selected from difunctional glycidyl ether epoxy resins, modified BPA-based epoxy resins, multifunctional epoxidized polybutadiene resins, or any combination thereof. The one or more flexible epoxy resins may independently have: an epoxy equivalent weight of about 260 to about 500 as measured according to ASTM D 1652-97; and / or a viscosity of about 700 cP to about 500,000 cP at 25°C as measured according to ASTM D445. The one or more flexible epoxy resins may be present in an amount of about 10 wt% to about 50 wt% of the A side; preferably about 35 wt% to about 45 wt% of the A side. The one or more flexible epoxy resins may include a difunctional glycidyl ether epoxy resin in an amount of about 10 wt % to about 18 wt % of the A side, an unmodified BPA-based epoxy resin in an amount of about 8 wt % to about 16 wt % of the A side, and a multifunctional epoxidized polybutadiene resin in an amount of about 8 wt % to about 16 wt % of the A side.

[0021] The one or more epoxy resins may include one or more epoxy phenol novolac resins. The one or more epoxy phenol novolac resins may have an epoxy equivalent weight of about 165 g / equivalent to about 183 g / equivalent as measured according to ASTM D1652-97; an average epoxy functionality of about 2.1 to about 6.5; and / or a viscosity of about 18,000 cP to about 30,000 cP at 25°C as measured according to ASTM D445.

[0022] The one or more epoxy phenol novolac resins may be present in an amount of about 30 wt % to about 50 wt % of the A side; preferably about 35 wt % to about 45 wt % of the first component or A side; more preferably about 38 wt % to about 42 wt % of the A side.

[0023] The one or more epoxy phenol novolac resins may include an about 3.6 functional epoxy phenol novolac resin present in an amount of about 2 wt % to about 18 wt % of the A side and an about 6.5 functional epoxy phenol novolac resin present in an amount of about 22 wt % to about 32 wt % of the A side; an about 3.6 functional epoxy phenol novolac resin present in an amount of about 15 wt % of the A side and an about 6.5 functional epoxy phenol novolac resin present in an amount of about 28 wt % of the A side; and / or an about 3.6 functional epoxy phenol novolac resin and an about 6.5 functional epoxy phenol novolac resin in a ratio of about 1:2 to about 1:3.

[0024] The one or more epoxy resins may include one or more aliphatic multifunctional epoxy resins; preferably epoxidized sorbitol. The one or more aliphatic multifunctional epoxy resins may have an epoxy equivalent weight of about 160 g / equivalent to about 195 g / equivalent as measured according to ASTM D1652-97; and / or a viscosity of about 200 cP to about 18,000 cP at 25°C as measured according to ASTM D445. The one or more aliphatic multifunctional epoxy resins may be present in an amount of about 5 wt % to about 20 wt % of the A side; preferably 8 wt % to about 16 wt % of the A side; more preferably about 10 wt % to about 14 wt % of the A side.

[0025] The one or more epoxy resins may include cashew nut shell liquid; preferably a glycidyl ether of cashew nut shell liquid; more preferably a glycidyl ether of cardanol. The one or more epoxy resins may include one or more reactive diluents; preferably polyethylene glycol diglycidyl ether, trimethylolethane triglycidyl ether, or both. The one or more reactive diluents may be present in an amount of about 5 wt % to about 20 wt % of the A side; preferably about 8 wt % to about 16 wt % of the A side; more preferably about 10 wt % to about 14 wt % of the A side.

[0026] The one or more epoxy resins may include one or more epoxy functional silanes or silane modified epoxy resins. The one or more silane modified epoxy resins may be present in an amount of about 1 wt % to about 15 wt % of the A side; preferably about 2 wt % to about 6 wt % of the A side; more preferably about 4 wt % of the A side.

[0027] The cured adhesive can provide an assembly having a lap shear of at least about 15MPa as measured according to EN2243-1. The adhesive can include calcium carbonate. The adhesive can include an elastomeric material. The adhesive can include one or more of calcium carbonate, a mineral, a reinforcing fiber, a hydrophobic silica, or any combination thereof. The adhesive can include calcium carbonate present in an amount of about 2% by weight to about 25% by weight of part A. The adhesive can include a core-shell material. The adhesive can include one or more liquid epoxy resins including a reaction product of epichlorohydrin and bisphenol A. The cured adhesive can have a tensile modulus of at least 1000MPa as measured according to ISO527.

[0028] Part A may include epoxidized linseed oil. Any component in Part B may not be physically separated from the acidic phosphorus-containing component. Part A and Part B may be substantially free of any fiber material. The epoxy resin may include an aliphatic epoxy resin. Part A may include epoxidized linseed oil in an amount greater than 0.5% but less than 10%. Part A may include epoxidized linseed oil in an amount greater than 1% but less than 6%. Part A may include bisphenol A epoxy resin in an amount of at least 0.5%.

[0029] Part A may include bisphenol A epoxy resin in an amount of at least 2.5%. Part A may include bisphenol A epoxy resin and epoxidized linseed oil in a ratio of about 1 part bisphenol A epoxy resin: 2 parts epoxidized linseed oil to about 2 parts bisphenol A epoxy resin: about 1 part epoxidized linseed oil. Part A may include bisphenol A epoxy resin and epoxidized linseed oil in a ratio of about 1 part bisphenol A epoxy resin: 1 part epoxidized linseed oil. Part A may include difunctional glycidyl ether epoxy resin and epoxidized linseed oil in a ratio of about 3 parts difunctional glycidyl ether epoxy resin: about 1 part epoxidized linseed oil. Part A and Part B may be present in a ratio of about 4 parts Part A to about 1 part Part B.

[0030] The adhesive may be cured at room temperature (about 20° C. to about 23° C.). The speed at which the adhesive cures may be increased with the addition of heat.

[0031] The teachings herein further relate to a method of adhering a first substrate to a second substrate, the method comprising positioning an adhesive on the first substrate and positioning the second substrate in contact with the adhesive within 5 minutes. Within 5 minutes of positioning the adhesive on the first substrate, part A of the adhesive may be mixed with part B of the adhesive. DETAILED DESCRIPTION

[0032] This teaching satisfies one or more of the above-mentioned needs through the improved compositions and methods described herein. The explanations and descriptions presented herein are intended to familiarize those skilled in the art with this teaching, its principles and its practical applications. Those skilled in the art can modify and apply this teaching in its various forms, such as being able to make it most suitable for the needs of a particular purpose. Therefore, the specific embodiments of this teaching set forth are not intended to be exhaustive or limit this teaching. Therefore, the scope of this teaching should not be determined with reference to the above description, but should be determined with reference to the full scope of the equivalents given by the attached claims and such claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. As will be understood from the following claims, other combinations are also possible, which are also incorporated by reference in this written specification.

[0033] This application claims the benefit of the filing date of U.S. Provisional Application Serial No. 63 / 334,350, filed on April 25, 2022. The contents of that application are incorporated herein by reference in their entirety and for all purposes.

[0034] The following teachings describe the overall performance of fast curing adhesives that are significantly improved by new non-traditional curing agent systems. For example, cross-linked epoxy resins made from traditional epoxy resins are known for their strength and stiffness, but are generally brittle, i.e., low strain failure materials, with poor impact resistance. This feature can produce adhesives with high shear strength when bonding metal substrates, but poor peel resistance and low fracture toughness. The low fracture toughness of these systems affects typically low peel resistance. No single ingredient can improve peel resistance alone. This may be the result of multiple ingredients and interactions, although the new curing agent systems used for these product types are important for maintaining reaction speed while obtaining improved peel resistance.

[0035] The teachings herein further describe the use of phosphoric acid and / or phosphate esters and / or other acidic ingredients such as carboxylic acids and anhydrides as primary activators to make two-component (A side and B side), room temperature curing adhesives. These adhesives can have some epoxy functionality, improved T-peel resistance and adhesion to various substrates. The key criterion is that the additional components in the curing agent side (B side) must be compatible with phosphoric acid or phosphate esters and not physically separated from the acid or phosphate ester. Generally, it is known that acids or any molecules that can be easily deprotonated initiate ring opening in epoxy resins and subsequent polymerization progression and crosslinking. The resulting molecular weight increase is essential for the mechanical and adhesive properties of the final product. Molecules with an average functionality greater than 2, whether they are proton-releasing molecules, epoxy-functional molecules, or any combination of the two, are able to produce a three-dimensional crosslinked network when reacted through their functional groups.

[0036] Side A can include one or more epoxy resins, one or more additives, one or more monomers or both. The one or more epoxy resins can include one or more liquid epoxy resins, one or more flexible epoxy resins, one or more epoxy phenol novolac resins, one or more aliphatic multifunctional epoxy resins, one or more reactive diluents, one or more silane-modified epoxy resins, one or more monomers or any combination thereof. The one or more additives can include one or more toughening agents (e.g., core-shell polymer microparticles), metal carbonates, minerals, reinforcing fibers, pyrogenic silica, plate-like alumina or any combination thereof.

[0037] The B side may include one or more phosphates, phosphoric acid, polyphosphoric acid, phosphorus pentoxide, one or more phosphorus-free acids or derivatives, one or more anhydrides, one or more additives, one or more monomers or any combination thereof. The one or more phosphates may include a first phosphate, a second phosphate, a third phosphate or any combination thereof. The one or more additives may include minerals, reinforcing fibers, pyrogenic silica or any combination thereof.

[0038] Phosphoric acid works well for initiation and propagation of epoxy crosslinks. However, there are difficulties in using this acid as the sole curing agent for some types of formulated products. Due to its low molecular weight and high functionality compared to the most common epoxy molecules, the volume mixing ratio between resin and curing agent may be too different. Typically, mixing ratios of 1:1 are most preferred in many cases because they are easy to handle and generally increase tolerance for off-ratio mixing. Mixing ratios of 2:1, 4:1, and even 10:1 may be acceptable, but higher mixing ratios necessitate more precise metering of inferior components.

[0039] The high functionality and low pH of phosphoric acid also contribute to a fast reaction rate. In an automated process, a fast-curing adhesive that cures in less than 5 minutes may be desirable. However, for most manual assembly processes, a certain amount of time is required to mix and apply the adhesive and subsequently assemble the parts. In addition, as previously mentioned, fast-curing adhesives have a performance tradeoff. The performance reduction is partly due to the reduced wetting time of the adhesive. That is, the time that the adhesive must be in close contact with the substrate before the molecular weight increases and the subsequent crosslinking begins is reduced. Rapid viscosity build-up may also be an obstacle to the formation of adhesion. Similarly, a fast reaction rate reduces the time available for phase separation of discrete secondary phases, which is useful for physical property improvements, particularly for increasing peel resistance, as will be discussed epoxidized carboxyl-terminated acrylonitrile-butadiene rubber.

[0040] Due to the rapid rate of bond formation caused by epoxy crosslinking, a high peak exotherm can occur if sufficient material mass is present. The same amount of energy can be released from a slower curing system, but the heat will have more time to dissipate or transfer to the substrate, surrounding materials, or air, reducing the peak exotherm.

[0041] U.S. Patent No. 6,730,713 describes a material comprising an epoxy resin, phosphoric acid and a metal carbonate for forming a foamed-in-place material, and WO 2016 / 149700 describes an esterified acid for a polymeric material. The teachings herein describe structural adhesives having improved T-peel resistance and desirable adhesion to a variety of substrate types. Although some of the following teachings describe non-foamed or minimally foamed materials, materials having a final density similar to the combination of the densities of the two initial components, more highly foamed materials can be made having a final density significantly less than the combination of the densities of the two initial components.

[0042] As described in WO 2016 / 149700, pre-reacting phosphoric acid with epoxy functional molecules can eliminate or reduce many of the difficulties associated with using concentrated phosphoric acid as the sole curing agent. Higher molecular weight molecules with reduced reactivity will react more slowly and have fewer reactive functional groups per unit volume, thereby reducing the peak exotherm of the reaction mixture. The combination of higher molecular weight and reduced reactivity may also affect the volume mixing ratio between the epoxy resin and the curing agent, making it closer to 1:1. In addition, the reaction product of phosphoric acid and epoxy resin is more viscous than phosphoric acid alone. This will typically more closely match the viscosity of the epoxy functional side and enable better mixing of the two. In addition, material properties and characteristics can be adjusted by selecting epoxy functional molecules for pre-reaction with phosphoric acid, allowing material properties to be obtained from a combination of both the resin component and the curing agent component of the adhesive. These properties of using phosphoric acid and / or esters of phosphoric acid enable the production of adhesives that react quickly but still adhere to a wide range of substrates.

[0043] According to the teachings of this article, phosphoric acid and / or esters of phosphoric acid can be used as curing agents. Other chemical structures can be combined with phosphoric acid or esters to improve the mechanical properties, bonding strength, processing properties and curing kinetics of the formulated product. Esters with neutral raw pH can also be used. In one embodiment, carboxylic acid functional components can be combined with curing agents. Anhydrides can also be added to the curing agent side of the preparation. These additives can be used because they contribute to the final material properties or adjust the pH of the curing agent part of the preparation. Epodi1LV5 (non-reactive xylene-formaldehyde diluent) is an example of being used in combination with phosphoric acid and / or phosphoric acid esters. Other non-reactive additives can also be used, whether they are organic or inorganic, such as minerals. Typically, inorganic thixotropes such as pyrogenic silica or clay are used to impart non-Newtonian rheological behavior. Organic thixotropes such as polymer fibers can also be used.

[0044] Phosphoric acid is reacted with epoxy resin to form a statistically monosubstituted acid-ester to reduce the average number of reactive hydrogens to 2 for further epoxy resin reactions. In order to form a crosslinked network, the average functionality of the system needs to be greater than 2, although it is not necessary to be much greater than 2. This can be achieved by adding a small amount of unreacted phosphoric acid, polyphosphoric acid or polyphosphate ester to the curing agent, or by using a multifunctional epoxy resin (i.e., an epoxy resin having more than two oxirane rings on the molecule). Phenol novolac resins or cresol novolac resins can be used for this purpose. Multifunctional aliphatic resins such as epoxidized soybean oil also work. In at least one embodiment of the present patent, unreacted phosphoric acid and multifunctional epoxy resins have been used in combination.

[0045] The one or more phosphates can be one or more customized phosphates. The one or more customized phosphates can be produced by the reaction of phosphoric acid and various alcohols. The one or more customized phosphates can be produced by the reaction of phosphoric acid with an epoxy group of a phosphate precursor (i.e., a component that has not yet reacted with phosphoric acid). The one or more customized phosphates can be produced by the reaction of phosphoric acid with a glycidyl ether of cashew nut shell liquid (CNSL) (such as those sold under the trade name LITE 2513HP, commercially available from Cardolite Corporation, Monmouth Junction NJ). The one or more customized phosphate esters can be produced by reacting phosphoric acid with phenyl glycidyl ether (such as those sold under the trade name The one or more customized phosphate esters can be produced by reacting phosphoric acid with 2-ethylhexyl glycidyl ether (such as sold under the trade name GE-13, commercially available from CVC Thermoset Specialties, Moorestown, NJ). The one or more customized phosphate esters can be produced by reacting phosphoric acid with epoxidized p-tert-butylphenol (such as epoxidized tert-butylphenol sold under the trade name GE-6, commercially available from CVC Thermoset Specialties, Inc., Moorestown, New Jersey). GE-11, commercially available from CVC Thermoset Specialties, Moorestown, N.J.) or any other monofunctional epoxy resin. The one or more customized phosphate esters can generally be the reaction product of phosphoric acid and a monoepoxy functional molecule.

[0046] The one or more phosphate esters may be one or more commercially available phosphate esters, typically made by reaction of various alcohols or unsaturated hydrocarbons with polyphosphoric acid and / or phosphorus pentoxide. When one or more commercially available phosphate esters are exchanged to the B side in place of a custom phosphate ester, they may produce a slower reacting and foaming curable composition due to lower levels of free phosphoric acid and therefore a higher pH on the B side. The reaction and foaming of the one or more commercially available phosphate esters can be improved (i.e., the reaction rate can be increased) by adding phosphoric acid to the B side. The one or more commercially available phosphate esters may have a pH of about 1 to about 4 in an aqueous solution. The one or more commercially available phosphate esters may have a viscosity of about 200 cP to about 42,500 cP at 25°C as measured according to ASTM D445. The one or more commercially available phosphate esters may be nonylphenol ethoxylated phosphate esters. The one or more commercially available phosphate esters may be butyl phosphate. An example of a suitable commercially available phosphate ester may be commercially available from Ashland, Inc. of Covington, KY, under the trade name Dextrol TM Those sold as OC-110, Dextrol OC-40, and Strodex MO-100. Another example of a suitable commercially available phosphate ester may be n-butyl acid phosphate commercially available from IsleChem of Grand Island, NY.

[0047] Commercially available phosphates may be present on the B side. The one or more commercially available phosphates may be present in an amount of about 5% to about 50% by weight of the B side. The one or more commercially available phosphates may be present in an amount of about 0.1% to about 30% by weight of the B side. The one or more commercially available phosphates may be present in an amount of about 10% to about 14% by weight of the B side. The one or more commercially available phosphates may be present in an amount of about 12% by weight of the B side.

[0048] The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid in a series of stoichiometric ratios. The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid at a ratio of about 0.7:1 to about 1:0.7. The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid at a ratio of about 0.8:1 to about 1:0.8. The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid at a ratio of about 0.9:1 to about 1:0.9. The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid at a ratio of about 1:1. The one or more phosphate esters can be produced by reacting a phosphate ester precursor with phosphoric acid at a ratio of about 0.8:1.

[0049] The one or more phosphoric acid esters may be selected from monoesters, diesters or triesters as shown below. The one or more phosphoric acid esters may be a combination of monoesters, diesters and triesters.

[0050]

[0051] The one or more phosphate esters can be obtained from the reaction of epoxy groups with phosphoric acid as shown below:

[0052]

[0053] The B side may include one or more phosphate esters, one or more phosphate ester precursors, or both. The B side may include one or more phosphate ester precursors, which may be combined with phosphoric acid prior to being combined with the A side. The B side may include one or more phosphate esters, which are pre-reacted (i.e., the epoxide and phosphate ester react) prior to being added to the B side.

[0054] The binder may include more than one type of phosphate ester. At least one phosphate ester may be a glycidyl ether of phosphoric acid and cashew nut shell liquid (CNSL) (e.g. LITE 2513HP). At least one phosphate ester can be a stoichiometric amount of about 1:1 2-ethylhexyl glycidyl ether (e.g., The at least one phosphate ester may be a stoichiometric ratio of 0.8:1 phosphoric acid to 2-ethylhexyl glycidyl ether (e.g., However, there are many possibilities for the first phosphate ester, the second phosphate ester or the third phosphate ester.

[0055] At least one phosphate ester may be present in an amount of about 10% to about 60% by weight of the B side. At least one phosphate ester may be present in an amount of about 25% to about 35% by weight of the B side. At least one phosphate ester may be present in an amount of about 28% to about 32% by weight of the B side. At least one phosphate ester may be present in an amount of about 32% by weight of the B side. At least one phosphate ester may be present in an amount of about 5% to about 40% by weight of the B side. At least one phosphate ester may be present in an amount of about 15% to about 25% by weight of the B side. At least one phosphate ester may be present in an amount of about 18% to about 22% by weight of the B side. At least one phosphate ester may be present in an amount of about 21% by weight of the B side. At least one phosphate ester may be present in an amount of about 10% to about 65% by weight of the B side. At least one ester may be present in an amount of about 35% to about 45% by weight of the B side. At least one phosphate ester may be present in an amount of about 42% by weight of the B side. The at least one phosphate ester may be present in an amount of about 58 wt % of the B-side. The at least one phosphate ester may be present in an amount of about 60 wt % of the B-side.

[0056] The B side may include phosphoric acid. The phosphoric acid may be orthophosphoric acid, polyphosphoric acid, or both. The phosphoric acid may be a free acid in one or more phosphate esters, an acid added independently of one or more phosphate esters, or both. Adding phosphoric acid to the B side may result in increased expansion (e.g., foaming) of the resulting reaction product. When the temperature is below 23° C., adding phosphoric acid to the B side may increase the reactivity of the two-part system to help maintain the desired expansion level, cure level, or both.

[0057] The independently added phosphoric acid may be in an aqueous solution in an amount of 85% or more (i.e., "reagent grade"). The independently added phosphoric acid may be present in an amount of about 1% to about 20% by weight of the B side. The independently added phosphoric acid may be present in an amount of about 2% to about 6% by weight of the B side. The independently added phosphoric acid may be present in an amount of about 4% by weight of the B side.

[0058] The one or more phosphates produced by the reaction of phosphoric acid and a phosphate precursor may include free acid. The one or more phosphates may have about 1% or more free acid, about 3% or more free acid, about 5% or more free acid, about 15% or less free acid, about 13% or less free acid, or even about 11% or less free acid.

[0059] After the A-side and B-side are added, the two-part system may foam due to the reaction of the metal carbonate or metal bicarbonate with the acid, resulting in the release of gas (e.g., carbon dioxide used as a chemical blowing agent). This reaction mechanism is described in U.S. Pat. No. 5,648,401, which is incorporated herein by reference for all purposes.

[0060] Reaction, foaming or both can occur at a temperature of about 70°C or less, about 50°C or less, about 30°C or less, about 20°C or less, or even about 0°C or less. Curing, foaming or both can occur at a temperature of about 0°C or more, about 10°C or more, or even about 20°C or more. Curing, foaming or both can occur at a temperature of about 10°C to about 35°C. Curing, foaming or both can occur at a temperature of about 10°C. Curing, foaming or both can occur at room temperature (e.g., at a temperature of about 15°C to about 25°C). Curing, foaming or both can occur at a temperature of about 23°C.

[0061] Compared with other curing agents or curing agent systems that occur when not adding stimulation (for example, at room temperature), this teaching contemplates relatively fast curing time, foaming time or both.The curing time of reaction product can be 30 minutes or less, 20 minutes or less, 2 minutes or more, 8 minutes or more or even 16 minutes or more.The curing time of gained reaction product can be about 5 minutes to about 20 minutes.The curing time of gained reaction product can be about 10 minutes.The curing time of gained reaction product can be about 7 minutes.The curing time of gained reaction product can be about 5 minutes.

[0062] Side A can include one or more epoxy functional materials (i.e., one or more epoxy resins). The one or more epoxy resins can be any conventional dimerization, oligomerization or polymerization epoxy resin. The one or more epoxy resins can contain at least one epoxy functional group (i.e., monofunctional) or can contain more than one epoxy functional group (i.e., multifunctional). The one or more epoxy resins can contain one or more epoxy functional groups, two or more epoxy functional groups, three or more epoxy functional groups or even four or more epoxy functional groups. The one or more epoxy resins can be modified epoxy resins (e.g., silane-modified, elastomer-modified, etc.). The one or more epoxy resins can be aliphatic, alicyclic, aromatic, etc. or any combination thereof. The one or more epoxy resins can be supplied as solid (e.g., as pellets, blocks, sheets, etc. or any combination thereof) or liquid (e.g., liquid epoxy resin). However, if solid resins are used, they are first dissolved in liquid resins or other suitable solvents. As used herein, unless otherwise specified, an epoxy resin is a solid resin if it is solid at a temperature of 23° C., and a liquid resin if it is liquid at a temperature of 23° C. The one or more epoxy resins may include one or more liquid epoxy resins, one or more flexible epoxy resins, one or more epoxy phenol novolac resins, one or more aliphatic multifunctional epoxy resins, one or more reactive diluents, one or more silane-modified epoxy resins, or any combination thereof.

[0063] The two-part system may include one or more liquid epoxy resins. The one or more liquid epoxy resins may serve as a base for the epoxy resin component. The one or more liquid epoxy resins may be the reaction product of epichlorohydrin (hereinafter referred to as "EPH") and any conventional bisphenol. The one or more liquid epoxy resins may be the reaction product of EPH and bisphenol A (hereinafter referred to as "BPA"), bisphenol F (hereinafter referred to as "BPF"), or both. The one or more liquid epoxy resins (which may be standard or commercial liquid epoxy resins) may have an epoxy equivalent weight (hereinafter referred to as "EEW") of about 100 g / equivalent to about 1000 g / equivalent as measured according to ASTM D1652-97. The one or more liquid epoxy resins may have an epoxy percentage of about 20 to about 25. The one or more liquid epoxy resins may have a viscosity of about 10 cP to about 100,000 cP at 25°C as measured according to ASTM D445. An example of a suitable BPA-based liquid epoxy resin may be DER TM 331, commercially available from The Olin Corporation, Clayton, MO. An example of a suitable BPF-based liquid epoxy resin may be YDF-170, commercially available from Kukdo Chemical (Korea).

[0064] The one or more liquid epoxy resins may be present as part of the A side. The one or more liquid epoxy resins may be present in an amount of about 4 wt % to about 50 wt % of the A side. The one or more liquid epoxy resins may be present in an amount of about 10 wt % to about 30 wt % of the A side. The one or more liquid epoxy resins may be present in an amount of about 8 wt % of the A side.

[0065] Epoxy resins produced by the reaction of epoxy resins with carboxyl terminated acrylonitrile-butadiene (hereinafter referred to as "CTBN") liquid rubbers have traditionally been used to impart impact resistance to epoxy matrices. Many publications inform us of their use to increase the K1C (fracture toughness value) of cured epoxy resins by creating discrete precipitated rubber domains within a rigid epoxy matrix. These discrete domains provide a tortuous path through the epoxy matrix for crack propagation, resulting in increased fracture resistance. They can also help dissipate fracture energy through cracks, the formation of multiple cracks, cavitation of rubber particles, debonding, and the formation of voids within the matrix. These resins typically lower the glass transition temperature (Tg) of the adhesive, although because not all of the rubber phase separates from the matrix, some of the rubber reacts with the epoxy resin.

[0066] Epoxy functionalized molecules such as epoxy functional polyurethanes can also contribute to improved peel resistance. These molecules can help increase the affinity of adhesives to certain substrates. These molecules can also increase the ability of the cross-linked network to absorb fracture energy by bending, flexing or local translation of molecular chains. These functionalized epoxy resins and epoxy resins produced by the reaction products of elastomers are generally referred to as modified epoxy resins.

[0067] Dimerized fatty acids are another group of epoxidized molecules that can improve the peel resistance of adhesives. The use of epoxidized fatty acids as epoxy resin tougheners and impact modifiers has increased over the past 10 years. These long-chain molecules with 36 carbon atoms in the chain provide molecular hydrocarbon character and impart lubricity and flexibility to the crosslinked network. Their hydrophobic nature tends to improve the adhesive's resistance to exposure to humid environments. In addition, less Tg reduction of the adhesive matrix is ​​observed compared to adhesives containing epoxidized CTBN.

[0068] The two-part system may include one or more flexible epoxy resins. The one or more flexible epoxy resins may function to reduce the elastic modulus of the reaction product, increase the failure strain, reduce the recovery time, reduce the degree of crosslink density in the reaction product, increase impact resistance, improve adhesion, improve peel resistance, or any combination thereof. The one or more flexible epoxy resins may partially improve the gas entrapment capacity of the two-part system by acting as a viscosity modifier or reducing gas permeability. The one or more flexible epoxy resins may be a difunctional glycidyl ether epoxy resin, a modified BPA-based epoxy resin, a multifunctional epoxidized polybutadiene resin, or any combination thereof. The one or more flexible epoxy resins may have an EEW of about 260 to about 500 as measured according to ASTM D1652-97. The one or more flexible epoxy resins may have a viscosity of about 700 cP to about 500,000 cP at 25°C as measured according to ASTM D445. Examples of suitable flexible epoxy resins may include NC-514 (commercially available from Cardolite Corporation of Monmouth Junction, New Jersey), PY 4122 (commercially available from Huntsman Advanced Materials, Inc., Salt Lake City, UT), Poly 605E (commercially available from Cray Valley, Exton, PA), or any combination thereof.

[0069] The one or more flexible epoxy resins may be present on the A side. The one or more flexible epoxy resins may be present in an amount of about 10% to about 50% by weight of the A side. The one or more flexible epoxy resins may be present in an amount of about 35% to about 45% by weight of the A side. The one or more flexible epoxy resins may be present in an amount of about 39% by weight of the A side. The one or more flexible epoxy resins may include a difunctional glycidyl ether epoxy resin in an amount of about 10% to about 18% by weight of the A side, an unmodified BPA-based epoxy resin in an amount of about 8% to about 16% by weight of the A side, and a multifunctional epoxidized polybutadiene resin in an amount of about 8% to about 16% by weight of the A side. The one or more flexible epoxy resins may include a difunctional glycidyl ether epoxy resin in an amount of about 14% by weight of the A side, an unmodified BPA-based epoxy resin in an amount of about 12% by weight of the A side, and a multifunctional epoxidized polybutadiene resin in an amount of about 12% by weight of the A side. The two-component system may include a difunctional glycidyl ether epoxy resin, a difunctional epoxy resin derived from cardanol, and a multifunctional epoxidized polybutadiene resin in a ratio of about 1:1:1. The two-component system may include a difunctional glycidyl ether epoxy resin, a difunctional epoxy resin derived from cardanol, and a multifunctional epoxidized polybutadiene resin in a ratio of about 1:0.8:0.8. The two-component system may include a difunctional glycidyl ether epoxy resin, a difunctional epoxy resin derived from cardanol, and a multifunctional epoxidized polybutadiene resin in a ratio of about 1:0.9:0.9.

[0070] The two-part system (adhesive) described herein may also include one or more epoxy phenol novolac resins (hereinafter referred to as "EPN"). The one or more epoxy phenol novolac resins may serve to impart chemical resistance, solvent resistance, temperature resistance, or any combination thereof to the reaction product. The one or more epoxy phenol novolac resins may be present as part of the A side. The one or more epoxy phenol novolac resins may have an EEW of about 165 g / equivalent to about 183 g / equivalent as measured according to ASTM D 1652-97. The one or more epoxy phenol novolac resins may have an average epoxy functionality of about 2.1 to about 6.5. A major function of EPN resins is to increase the network crosslinking density through multifunctionality. This is also important for controlling the reaction rate and the ability to prevent foam collapse during and / or after the reaction process. The one or more epoxy phenol novolac resins may have a viscosity of about 18,000 cP to about 30,000 cP at 25°C as measured according to ASTM D445. Examples of suitable epoxy phenol novolac resins are those sold under the trade names Epalloy 8250 and Epalloy 8330, commercially available from CVC Thermoset Specialties, Inc. of Moorestown, New Jersey.

[0071] The one or more epoxy phenol novolac resins may be present in an amount of about 30% by weight to about 50% by weight of the A side. The one or more epoxy phenol novolac resins may be present in an amount of about 35% by weight to about 45% by weight of the first component or the A side. The one or more epoxy phenol novolac resins may be present in an amount of about 38% by weight to about 42% by weight of the A side. The one or more epoxy phenol novolac resins may be present in an amount of about 42% by weight of the A side. The one or more epoxy phenol novolac resins may include an approximately 3.6-functional epoxy phenol novolac resin present in an amount of about 2% by weight to about 18% by weight of the A side and an approximately 6.5-functional epoxy novolac resin present in an amount of about 22% by weight to about 32% by weight of the A side. The one or more epoxy phenol novolac resins may include an about 3.6 functional epoxy phenol novolac resin present in an amount of about 15 wt % of the A side and an about 6.5 functional epoxy novolac resin present in an amount of about 28 wt % of the A side. The two part system may include an about 3.6 functional epoxy phenol novolac resin and an about 6.5 functional epoxy phenol novolac resin in a ratio of about 1:2 to about 1:3.

[0072] Another way to increase the fracture toughness of epoxy adhesives is by using aliphatic epoxy resins, or resins with saturated long carbon chains between the epoxy rings. Products such as Erisys EDGE from Huntsman-CVC and cardanol-based products from Cardolite provide improved fracture resistance through their increased chain flexibility. Epoxidized oils, such as but not limited to soybean oil or linseed oil, which may be aliphatic in nature, can provide increased resistance to peeling. In addition, the long carbon chains between the functional groups create an adhesive matrix that can better conform to deformation through a large plastic deformation zone, thus absorbing some of the fracture energy.

[0073] The adhesive may include one or more aliphatic multifunctional epoxy resins. The one or more aliphatic multifunctional epoxy resins may serve to increase the degree of crosslinking of the reaction product, increase the chemical resistance of the reaction product, or both. These resins have the ability to increase the crosslinking density of the resulting reaction product while maintaining or enhancing the elastomeric properties of the reaction product. The multifunctional material may give the reaction product less elasticity. The one or more aliphatic multifunctional epoxy resins may include epoxidized sorbitol. The one or more aliphatic multifunctional epoxy resins may have an EEW of about 160 g / equivalent to about 195 g / equivalent as measured according to ASTM D1652-97. The one or more aliphatic multifunctional epoxy resins may have a viscosity of about 200 cP to about 18,000 cP at 25° C. as measured according to ASTM D445. Examples of suitable aliphatic multifunctional epoxy resins may be those sold under the trade name GE-60 and Those sold as GE-61, commercially available from CVC Thermoset Specialties, Inc., of Moorestown, NJ, or Epoxol 9-5, commercially available from ACS Technical Products, of Griffith, IN.

[0074] The one or more aliphatic multifunctional epoxy resins may be present as part of the A side. The one or more aliphatic multifunctional epoxy resins may be present in an amount of about 5% to about 20% by weight of the A side. The one or more aliphatic multifunctional epoxy resins may be present in an amount of about 8% to about 16% of the A side. The one or more aliphatic multifunctional epoxy resins may be present in an amount of about 10% to about 14% of the A side. The one or more aliphatic multifunctional epoxy resins may be present in an amount of about 12% by weight of the A side.

[0075] The binder may include cashew nut shell liquid (hereinafter referred to as "CNSL"), which may include chemicals commonly extracted from cashew nut shell liquid (CNSL), including anacardic acid, cardol, cardanol, or any combination thereof. Preferably, the glycidyl ether of cashew nut shell liquid (CNSL) is the glycidyl ether of cardanol.

[0076] Formulated materials containing cardanol derivative products, such as those available from Cardolite, such as NC-514, also exhibit improved adhesion to metal substrates, particularly metal substrates that are not surface treated or cleaned when contaminated with organic matter. The long aliphatic chains within the molecule are believed to be able to compatibilize or solubilize surface contaminants, such as stamping oils, protective coatings, or mold release agents, making these surfaces more available for bonding.

[0077] The use of core-shell (hereinafter "CS") particles also helps reduce or retard fracture propagation through the adhesive. CS particles help increase fracture toughness in much the same manner as CTBN-adducted epoxies by incorporating preformed elastomeric particles having a rigid shell and a flexible core into a rigid matrix. However, because they do not react into a crosslinked network, the typical reduction in cure Tg observed with modified or flexible epoxies is smaller or non-existent. CS particles are particularly advantageous in fast-curing adhesives because they exist as discrete particles and do not require a secondary process such as reaction-induced phase separation (hereinafter "RIPS") to impart toughness to the polymer matrix. RIPS toughened adhesives generally benefit from slower reaction times, which allow a secondary phase to form as the primary phase crosslinks. A rapid reaction may not allow time for the secondary phase to form. If the secondary phase does not precipitate, a lower Tg can be expected and less favorable for physical property improvements.

[0078] The adhesive may include one or more additives. The one or more additives may include one or more toughening agents, calcium carbonate, minerals, reinforcing fibers, fumed silica, platy alumina, or any combination thereof.

[0079] As mentioned above, adhesive can include one or more tougheners.The one or more tougheners can play the effect of distributing energy in the reaction product (that is, increasing impact resistance).The one or more tougheners can facilitate the T peel strength of increase.The one or more tougheners can include thermoplastics, thermosetting plastics or thermosetting plastics, elastomers etc. or any combination thereof.The one or more tougheners can include elastomers (including elastomer-containing materials), core-shell polymers (which can include but are not limited to elastomers) or both.

[0080] Core-shell polymers can include a first polymer material (i.e., core material) and a second polymer material (i.e., shell material). The first polymer material can be completely encapsulated by the second polymer material. Core-shell polymers can include a first polymer material in an amount of about 30 wt % or more, 50 wt % or more, or even 70 wt % or more. The first polymer material, the second polymer material, or both can include one, two, three, or even more than three polymers combined together, reacted together (e.g., sequentially polymerized) or both, or can be a part of a separate or identical core-shell polymer system. The example of a suitable core-shell polymer can be one of the polymers known under the trade name Kane Ace TM Those sold as MX-267 and MX-257 (both commercially available from Kaneka North America LLC, Pasadena, TX).

[0081] Core-shell polymers can be present in an amount of about 1% by weight to about 25% by weight of a combination of side A, side B, or side A and side B (e.g., if present in an amount of 10% by weight, it can be present in an amount of 5% by weight to 5% by weight of side A and side B). Core-shell polymers can be present in an amount of about 5% by weight to about 20% by weight of a combination of side A, side B, or side A and side B. Core-shell polymers can be present in an amount of about 5% by weight to about 5% by weight of a combination of side A, side B, or side A and side B. Core-shell polymers can be present in an amount of about 17% by weight of a combination of side A, side B, or side A and side B.

[0082] The adhesive may include one or more reactive diluents. The one or more reactive diluents may act to reduce the overall viscosity of the two-part system in order to modify the dispensing process or the flow of the two-part system on the workpiece after dispensing, and when the diluent is monofunctional, the degree of crosslinking is reduced. When the diluent statistically exceeds the bifunctionality, the diluent may increase the crosslinking density. The one or more reactive diluents may be polymeric, whereby the reactive diluent may increase the flexibility of the reaction product; the one or more reactive diluents may be multifunctional, whereby the reactive diluent may promote increased crosslinking and impart chemical resistance to the reaction product; or both. The one or more reactive diluents may include polyethylene glycol diglycidyl ether, trimethylolethane triglycidyl, or both. The one or more reactive diluents may have an EEW of about 100 g / equivalent to about 300 g / equivalent as measured according to ASTM D1652-97. The one or more reactive diluents may have a viscosity of about 10 cP to about 1000 cP at 25 ° C as measured according to ASTM D445. Examples of suitable reactive diluents may be found under the trade name GE-31 and Those sold as GE-24 are commercially available from CVC Thermoset Specialties, Inc. of Moorestown, New Jersey.

[0083] The one or more reactive diluents may be present in an amount of about 5% to about 20% by weight of the A side. The one or more reactive diluents may be present in an amount of about 8% to about 16% by weight of the A side. The one or more reactive diluents may be present in an amount of about 10% to about 14% by weight of the A side. The one or more reactive diluents may be present in an amount of about 13% by weight of the A side. The one or more reactive diluents may include polyethylene glycol diglycidyl ether present in an amount of about 2% to about 6% by weight of the A side, and trimethylolethane triglycidyl ether present in an amount of about 6% to about 14% by weight of the A side. The one or more reactive diluents may include polyethylene glycol diglycidyl ether present in an amount of about 4% by weight of the A side, and trimethylolethane triglycidyl ether present in an amount of about 9% of the A side. The two-part system may include polyethylene glycol diglycidyl ether and trimethylolethane triglycidyl ether in a ratio of about 1:2 to about 1:3, respectively.

[0084] The adhesive may include one or more epoxy-functional silanes or silane-modified epoxy resins. The one or more epoxy-functional silanes or silane-modified epoxy resins may serve to impart improved adhesion to the reaction product, particularly to glass, metal, or both. An example of a suitable epoxy-functional silane may be an epoxy-functional silane sold under the trade name Silquest A-187, commercially available from Momentive Performance Materials of Albany, NY. An example of a suitable silane-modified epoxy resin may be an epoxy-functional silane sold under the trade name Silquest A-187, commercially available from Momentive Performance Materials of Albany, NY. KSR-177 is a silane-modified epoxy resin sold commercially available from Kukdo Chemical (Korea). Another suitable material is a silicone prepolymer having alicyclic epoxy groups. An example of such a material is available from Siltech Corporation of Ontario, Canada under the trade name Silmer EPC Di-50.

[0085] The one or more silane-modified epoxy resins may be present on the A side. The one or more silane-modified epoxy resins may be present in an amount of about 1 wt % to about 15 wt % of the A side. The one or more silane-modified epoxy resins may be present in an amount of about 2 wt % to about 6 wt % of the A side. The one or more silane-modified epoxy resins may be present in an amount of about 4 wt % of the A side.

[0086] The adhesive may include one or more monomers. The one or more monomers may serve to improve the adhesion properties of the reaction product (particularly to metal substrates), increase the flexibility of the reaction product, increase the impact resistance of the reaction product, or any combination thereof. The one or more monomers may be monofunctional, difunctional, or even multifunctional. The one or more monomers may be the esterification product of an alcohol and acrylic acid or methacrylic acid. The one or more monomers may be monofunctional acrylic monomers. Preferably, the one or more monomers may be a mixture of methacrylate and 2-(2-ethoxyethoxy)ethyl acrylate. An example of a suitable monomer may be a monomer sold under the trade name SR 9050, commercially available from Sartomer of Exton, PA.

[0087] Adhesive can include one or more monomers in A side, B side or both.The one or more monomers can exist in an amount of about 0.1 % by weight to about 26 % by weight of a combination of A side, B side or both A side and B side.The one or more monomers can exist in an amount of about 12 % by weight to about 24 % by weight of a combination of A side, B side or both A side and B side.The one or more monomers can exist in an amount of about 14 % by weight to about 22 % by weight of a combination of A side, B side or both A side and B side.The one or more monomers can exist in an amount of about 18 % by weight of a combination of A side, B side or both A side and B side.

[0088] The cure rate, degree of crosslinking, or both may be a function of the functionality of the two-part system (A side and B side). For two-part systems with prepolymer components of shorter polymer length (i.e., lower viscosity), higher functionality (i.e., the average number of functional groups on one or more polymerizable components) may be desirable; thus, the lack of structural backbone caused by the shorter polymers is compensated by a higher degree of crosslinking. For two-part systems with prepolymer components of longer length (i.e., generally resulting in higher viscosity), lower functionality may be desirable; thus, the presence of more structural backbone caused by the longer polymers obviates the need for high functionality.

[0089] The B-side functionality can be reduced at least in part by reaction of the metal carbonate in the A-side with phosphoric acid and phosphate esters, thus reducing the functionality of the B-side. The A-side can include components with increased functionality to compensate for the reduced functionality of the B-side. The A-side can be formulated with increased functionality by using reactive ingredients with a functionality greater than 2.

[0090] As described in U.S. Patent No. 6,730,713, when metal carbonate is exposed to phosphoric acid and / or phosphoric acid ester in the presence of epoxy resin, foam can be produced by releasing carbon dioxide during the curing process. The porous structure in the adhesive or adhesive after foaming can help improve peel resistance. The cohesive failure in the adhesive after foaming is easier to achieve usually because the generation of pores can weaken the polymer body. Once the cohesive failure mode has been caused, the failure mode usually remains cohesive, partly due to the reduction of the force arm length and the change of the load angle, causing the crack to advance more slowly. Cohesive failure drives the fracture path through the adhesive, rather than at the junction of the adhesive and the substrate, resulting in higher resistance, shorter crack propagation distance, and therefore generally higher peel strength.

[0091] The reaction of calcium carbonate and acid neutralizes some of the acid. Modifying the acid equivalent of the mixed product in this way will reduce the crosslink density of the adhesive and change the mechanical properties. Calcium carbonate or another metal carbonate can be added directly to the curing agent mixture to change the acidity of the mixed composition. With a fixed volume ratio between the resin and the curing agent, neutralizing the acid in this way allows for variations between the acid equivalent and the epoxy equivalent in the mixed adhesive.

[0092] Adhesive can comprise one or more metal carbonates.These one or more metal carbonates can play the effect of producing gas, acting as filler, controlling the beginning or total extent of foaming (for example, expansion) process or both in the presence of acid.These one or more metal carbonates can be metal carbonate or metal bicarbonate.The example of suitable filler comprises calcium carbonate, nickel carbonate, barium carbonate, sodium bicarbonate and potassium bicarbonate.Preferably, these one or more metal carbonates can comprise calcium carbonate.Metal carbonate, metal bicarbonate or the particle size of both can control the expansion and solidification of two-part system, and thus the total surface area that can be used for metal carbonate, metal bicarbonate or both reacting with acid is the function of the particle size of metal carbonate, bicarbonate or both and the amount present in two-part system.

[0093] Calcium carbonate may be present as one or more calcium carbonate fillers. The one or more calcium carbonate fillers may have a median particle size of about 1 to about 50 microns. The calcium carbonate may be medium fine particle size. For example, the median particle size of medium fine calcium carbonate may be about 22 microns. Examples of suitable medium fine calcium carbonate may be Q200, commercially available from Huber Engineered Materials of Atlanta, GA. The calcium carbonate may be finely sized. For example, the median particle size of the fine calcium carbonate may be about 4 microns. An example of a suitable fine calcium carbonate may be Q4, commercially available from Huber Engineered Materials in Atlanta, Georgia. The calcium carbonate can be ultrafine sized. For example, the median particle size of the ultrafine calcium carbonate can be about 1 micron. An example of a suitable ultrafine calcium carbonate can be Q2, commercially available from Huber Engineered Materials, Atlanta, Ga. The two-part system may include medium fine calcium carbonate, fine calcium carbonate, ultrafine calcium carbonate, or any combination thereof.

[0094] Calcium carbonate may be present in an amount of about 1% to about 25% by weight of the A side. Calcium carbonate may be present in an amount of about 4% to about 18% by weight of the A side. Calcium carbonate may be present in an amount of about 8% to about 12% by weight of the A side. Calcium carbonate may be present in an amount of about 20% by weight of the A side. Calcium carbonate may include fine calcium carbonate present in an amount of about 4% to about 8% by weight of the A side and medium fine calcium carbonate present in an amount of about 13% to about 18% by weight of the A side. Calcium carbonate may include fine calcium carbonate present in an amount of about 6% by weight of the A side and medium fine calcium carbonate present in an amount of about 15% by weight of the A side. Calcium carbonate may include fine calcium carbonate present in an amount of about 5% by weight of the A side and medium fine calcium carbonate present in an amount of about 5% by weight of the A side. The ratio of medium fine calcium carbonate to fine calcium carbonate may be about 3:1 to about 1:3. The ratio of medium fine calcium carbonate to fine calcium carbonate may be about 1:1.

[0095] The calcium carbonate may include a coating. The coating may be any material that decomposes during the activation process, the expansion process, or both processes, such that expansion is delayed, slowed, or both. The coating may be a wax, a fatty acid, or a combination thereof.

[0096] The adhesive can include one or more minerals. The one or more minerals (i.e., "mineral reinforcement") can play a role in structurally strengthening the reaction product. The one or more minerals can improve the tensile strength, flexural strength or both of the reaction product. The one or more minerals can be any suitable silicate minerals, including but not limited to chain silicates (e.g., wollastonite) and phyllosilicates (e.g., kaolinite, vermiculite, talc, muscovite, etc.). The characteristic external shape of the single crystal or crystal group of the one or more minerals can be needle-like or needle-like. The median particle size of the one or more minerals can be about 10 microns to about 20 microns. The median particle size can be about 12 microns to about 18 microns.

[0097] The adhesive may include one or more reinforcing fibers. The reinforcing fibers may serve to structurally reinforce the reaction product. The one or more reinforcing fibers may improve the tensile strength, flexural strength, or both of the reaction product. The one or more reinforcing fibers may be present in the A side, the B side, or both. The one or more reinforcing fibers may be uniformly dispersed in the A side, the B side, or both. The one or more reinforcing fibers may comprise polymer fibers, glass fibers (i.e., fiberglass), or both. The polymer fibers may include nylon, polyamide, polyester, polypropylene, polyethylene, polytetrafluoroethylene, aramid fibers (e.g., ) or the like, or any combination thereof. The glass fibers may include aluminoborosilicate glass ("E-glass"), alkali-lime glass ("A-glass" or "C-glass"), electrically / chemically resistant glass ("E-CR-glass"), borosilicate glass ("D-glass"), aluminosilicate glass ("R-glass" or "S-glass"), or any combination thereof. The reinforcing fibers may be chopped fibers. The reinforcing fibers may be chopped into lengths of about 0.1 cm or greater, about 0.3 cm or greater, or even about 0.6 cm or greater. The reinforcing fibers may be chopped into lengths of about 2.0 cm or less, about 1.5 cm or less, or even about 1.0 cm or less. An example of a suitable glass fiber may be chopped strands commercially available from Jushi USA in Columbia, SC.

[0098] Reinforcement fiber can exist with the amount of about 0.01 % by weight to about 3 % by weight of the combination of A side, B side or A side and B side. Reinforcement fiber can exist with the amount of about 0.1 % by weight to about 1 % by weight of the combination of A side, B side or A side and B side. Reinforcement fiber can exist with the amount of about 0.2 % by weight of the combination of A side, B side or A side and B side. Two-part system can include one or more thixotropes to control viscosity.

[0099] The two-part system can include a hydrophobic silica. The hydrophobic silica can play a role in controlling viscosity (e.g., thickening), controlling thixotropy, enhancing hydrophobicity, or a combination thereof. The hydrophobic silica can be a fumed silica. The hydrophobic silica can be surface treated. For example, the hydrophobic silica can be a fumed silica surface treated with polydimethylsiloxane (hereinafter referred to as "PDMS") or hexamethyldisilazane (hereinafter referred to as "HMDZ"). The hydrophobic silica can be present as part of the A side, the B side, or both. Examples of suitable hydrophobic silicas can be those sold under the trade name Hydrophobic silica sold under the trade names R 202, commercially available from Evonik Corporation of Parsippany, New Jersey; and Those sold as TS-530 and TS-720 are commercially available from Cabot Corporation in Boston, MA.

[0100] Hydrophobic silica may be present in an amount of about 0.25% to about 6% by weight of the A side, the B side, or a combination of the A side and the B side. Hydrophobic silica may be present in an amount of about 0.5% to about 4% by weight of the A side, the B side, or a combination of the A side and the B side. Hydrophobic silica may be present in an amount of about 1% to about 2% by weight of the A side, the B side, or a combination of the A side and the B side. Hydrophobic silica may be present in an amount of about 0.5% to about 2% by weight of the A side. Hydrophobic silica may be present in an amount of about 3% to about 5% by weight of the B side. The ratio of hydrophobic silica in the A side to the B side may be about 1:6 to about 6:1. The ratio of hydrophobic silica in the A side to the B side may be about 1:4. The ratio of hydrophobic silica in the A side to the B side may be about 1:2 to about 2:1.

[0101] The two-part system can include tabular alumina. Tabular alumina can serve to impart hardness, thermal shock resistance, mechanical shock resistance, high heat capacity, high electrical resistance, or any combination thereof to the reaction product. Tabular alumina can be present in the A side, the B side, or both. Tabular alumina can be alpha alumina converted to its corundum form (i.e., crystalline alumina) and sintered, and can be provided as graded particles or powders. Tabular alumina can be graded (i.e., separated by size) to about 44 microns to about 4760 microns. Tabular alumina can be graded to about 44 microns.

[0102] The tabular alumina may be present in an amount of about 0.1 wt % to about 15 wt % of the A side, the B side, or a combination of both the A side and the B side. The tabular alumina may be present in an amount of about 4 wt % to about 12 wt % of the A side, the B side, or a combination of both the A side and the B side. The tabular alumina may be present in an amount of about 5 wt % of the A side. The tabular alumina may be present in an amount of about 10 wt % of the A side.

[0103] The adhesive may include one or more functional additives for improving one or more different properties of the composition. Examples of suitable functional additives may include antioxidants, antiozonants, ultraviolet absorbers, antistatic agents, colorants, coupling agents, curing agents, flame retardants, foaming agents, thermal stabilizers, impact modifiers, lubricants, plasticizers, preservatives, processing aids, stabilizers, etc. and any combination thereof.

[0104] The viscosity of the A side, the B side, or both can be high enough at about 23°C to prevent the two-part system from undesirably flowing into an area adjacent to the dispensed bead when dispensing the two-part system onto a workpiece, or to control the flow into an area adjacent to the dispensed bead when dispensing the two-part system (i.e., to allow a desired amount of flow). The viscosity of the A side, the B side, or both required to prevent undesirable flow or control flow can depend on the size of the beads being dispensed. For example, the thicker the bead of the two-part system being dispensed, the higher the viscosity required to prevent undesirable flow or control flow. At very low shear rates approaching sagging conditions, the viscosity of the A side at 23°C can be about 5,000 cP to about 50,000 cP or even about 35,000 cP to about 45,000 cP. The viscosity of the A side and the B side at 23°C can be about 250,000 cP to about 400,000 cP. The viscosity of the A side at 10° C. can be about 280,000 cP to about 350,000 cP or even about 300,000 cP to about 325,000 cP. The viscosity of the B side at 23° C. can be about 2,500 cP to about 50,000 cP or even about 35,000 cP to about 45,000 cP. The viscosity of the B side at 10° C. can be about 130,000 cP to about 220,000 cP or even about 175,000 cP to about 195,000 cP.

[0105] After mixing the A side and the B side, the adhesive can foam more than about 50%, more than about 100%, more than about 200%, less than about 800%, less than about 700%, or even less than about 600% based on the original volume of the two-part system. The two-part system can expand from about 400% to about 500% of the original volume of the two-part system. The two-part system can expand about 100% of the original volume of the two-part system. The adhesive can be substantially free of any foam.

[0106] The adhesive may be free of a curing agent (i.e., a conventional curing agent), a curing accelerator, or both. Typical curing agents include Lewis bases (i.e., anionic catalysts), Lewis acids (i.e., cationic catalysts), UV catalysts, amines, anhydrides, phenols, thiols, or any combination thereof. Instead of the above-mentioned curing agents, the two-part system can be cured after a polymerization reaction between a phosphoric acid-catalyzed phosphate and an epoxy group, a hydroxyl group, or both. The two-part system can both cure and expand through the chemical interaction between the phosphate and the metal carbonate. It has been found that the complexity of the formulation can be reduced by reducing the number of overall components (i.e., curing agent, curing accelerator, and blowing agent) using the curing and expansion system disclosed herein; however, achieving the desired expansion and curing time makes optimization more challenging.

[0107] The two part system can be mixed together at a ratio of 1:4 to 4:1 side A to side B. The two part system can be mixed together at a ratio of 1:2 to 2:1 side A to side B. The two part system can be mixed together at a ratio of 1:1 side A to side B. The two part system can be mixed together at a ratio of 2:1 side A to side B.

[0108] The adhesive may be cured and / or expanded before or after the workpieces are fully assembled, and the adhesive is applied to the workpieces. For example, the adhesive may be dispensed on a first workpiece, cured and / or expanded, and then a second workpiece complementary to the first workpiece may be applied to the first workpiece. As another embodiment, the adhesive may be dispensed on a first workpiece, a second workpiece complementary to the first workpiece may be applied to the first workpiece, and then the two-part system may be cured and / or expanded. The adhesive that is cured and / or expanded after the workpieces are fully assembled may expand to fill the space between the first workpiece and the second workpiece. The first workpiece, the second workpiece, or both may include a groove, and the adhesive is dispensed in the groove, expanded in the groove, or both. The two-component material may be dispensed in a cavity.

[0109] Table 1 provides the test results of typical commercially available 5-minute epoxy adhesives. According to ASTM D1876, T-peel resistance is measured by dividing the average of the forces required to separate the bonded substrates from each other at 180° by the bond width, and is usually given in Newtons / millimeter (N / mm) or pounds / inch (lb / in). T-peel samples were tested at 100mm / min. Lap shear samples were tested at 50mm / min according to EN 2243-1 testing. Tensile samples were tested at 10mm / min according to ISO 527. In contrast to Tanδ measured by DMA, Tg values ​​are obtained from the peak of G'. This value indicates where the material properties will begin to change.

[0110] Table 1: Physical properties of commercially available fast-curing structural adhesive materials

[0111]

[0112]

[0113] Lap shear results were very good for the plated steel specimens with JB Weld, but were significantly reduced for the galvanized and aluminum substrates. Lap shear results for Devcon 5 minutes, Gorilla glue 5 minutes, and ScotchWeld were less than expected for a structural adhesive.

[0114] According to the test standard, the peel strength is calculated by the average force per unit width after the first 10mm displacement from the initial peak force. A fragile T-peel bond indicates that the substrates quickly and suddenly debond before or shortly after reaching this displacement. The failure mode is represented by the percentage of cohesive failure (CF), which means that the amount of adhesive remaining attached to each substrate after the test is almost equal. When most of the adhesive remains on one substrate, but a film or thin coating of the adhesive remains on the second substrate, it is classified as surface cohesive failure (TCF). When most of the adhesive remains bonded to one substrate and no adhesive remains on the second substrate, it is classified as adhesive failure (AF).

[0115] The following examples describe the use of phosphoric acid and / or phosphate esters and / or other acidic components as the primary curing agent and a mixture containing epoxy functional materials (including bisphenol-A, bisphenol-F, aliphatic epoxy resins and elastomer-modified epoxy resins) as the primary resin to produce a two-component room temperature curing adhesive having some epoxy functional groups, which is particularly characterized by improved T-peel resistance.

[0116] Table 2

[0117]

[0118]

[0119]

[0120] Table 2 contains formulation examples with variations of epoxy resins containing an A side and a common curing agent B side. While these examples contain many of the components described herein and are considered to be within the scope of the present teachings, Example 1 exhibits some better physical characteristics when compared to Examples 2 to 6. In Example 1, we observed peel values ​​of at least 5 N / mm in either cohesive or thin cohesive failure modes on various substrates. In Example 2, while the failure mode for some substrates remained cohesive, the peel values ​​were reduced in the absence of calcium carbonate. On a galvanized steel substrate, the adhesive failed before any measurable peel occurred, demonstrating a weak bond. The stick / slip failure mode represents peel performance in terms of areas of highly variable bond strength.

[0121] Calcium carbonate can reduce the cohesive strength within the resin matrix, causing failure within the adhesive rather than at the interface between the adhesive and the substrate. The reaction of calcium carbonate with the acidic curing agent will consume some of the acidic reactive sites, possibly producing less overall crosslinking in the system. The reaction is also most likely to slow the crosslinking reaction by reacting the most acidic hydrogen atoms first and produce carbon dioxide gas. The slower crosslinking rate allows more time for the adhesive to wet to the substrate and creates a porous structure within the adhesive, both of which tend to improve peel resistance.

[0122] Compared to Example 1, in Example 3, the multifunctional aliphatic resin was removed, and the percentage of all raw materials increased proportionally with the removal of this component. This resulted in an increase in the lap shear value, but a decrease in the peel value and a decrease in the tensile elongation, while the tensile modulus increased. When one of the bis-A epoxy resins was removed, the overall strength of the system in Example 4 was reduced compared to Example 1. Reduced tensile properties were observed as well as reduced lap shear and peel values. In Example 5, the system exhibited a more fragile peel response, which was demonstrated by the reduction in all measured peel values. In this batch, the multifunctional epoxidized linseed oil was replaced by multifunctional epoxidized sorbitol. Compared to Example 1, in Example 6, epoxidized polypropylene glycol was used to replace the bis-A epoxy resin. Comparing Example 6 with Example 1, the tensile modulus decreased and the elongation increased significantly. A general decrease in the bond strength of the electroplated steel and the fragile behavior during peeling were also measured. Comparing Example 6 to Example 4, where epoxidized polypropylene glycol was added to this example, the tensile modulus again decreases with increasing elongation. Again, the peel performance of the electroplated steel decreases, however, slight increases in the lap shear and peel of the other substrates are observed.

[0123] Table 3

[0124]

[0125]

[0126] In Examples 7 and 8, the effect of epoxidized linseed oil on adhesive properties was evaluated. In Example 7, all of the phenol novolac resin was replaced with epoxidized linseed oil. However, a resin with more molecular mobility than the novolac resin was used, which increased the overall crosslink density of the system. The failure mode in peel shifted toward adhesive failure, and typically, strength was reduced. Compared to Example 1, a 20% increase in epoxidized linseed oil as shown in Example 8 resulted in a significant increase in lap shear values, but reduced peel results. However, compared to Example 7, the failure mode remained cohesive at this level.

[0127] Example 9 represents another embodiment of the present teachings. As with the previous examples, phosphoric acid and esters of phosphoric acid are used to crosslink a mixture of aromatic, aliphatic and impact-modified epoxy resins with CS microparticles to produce an adhesive with improved peel resistance. Example 9 illustrates another ratio of phosphoric acid to esterifying acid for producing these types of adhesives. These ratios are partially altered by using carboxylic acid terminated polymers.

[0128] Table 4

[0129]

[0130]

[0131]

[0132] In Examples 10 to 12 of Table 4, the importance of raw materials was evaluated by systematically removing them. In Examples 13 and 14, the effect of polymer fibers on the properties of the adhesive was evaluated. In Example 10, CS was removed compared to Example 1, allowing the other raw material percentages to remain in the same relative ratios to each other. Because the Kane Ace product is a 37% dispersion of CS in a liquid epoxy resin, YD-128 has been added to the formulation to compensate for the loss of resin. In the absence of CS particles, the adhesive is more brittle. Higher tensile modulus was measured with increased lap shear and significantly reduced peel performance. Lower cohesive failure was also noted.

[0133] All aliphatic epoxy resins were removed from Example 11 compared to Example 1. A significant increase in tensile modulus and a decrease in tensile elongation were measured. Adhesive performance was also significantly reduced in lap shear and T-peel on each substrate. In Example 12, the epoxidized polyurethane resin was removed compared to Example 1. All measured properties were reduced.

[0134] The fumed silica on the resin side and the Garamite on the curing agent side were removed from Example 12 and mostly replaced with polymer fibers to produce Example 13. Increased lap shear and peel properties were measured, especially on galvanized steel. Example 14 was produced by adding fibers to the A and B sides of Example 1. In this example, the lap shear values ​​remained similar, but both the tensile and T-peel properties were reduced.

[0135] The present teaching provides a method which may include: providing a two-part system comprising an A side (i.e., a first component) and a B side (i.e., a second component). The A side comprises one or more epoxy resins, and the B side comprises one or more phosphate esters and optionally phosphoric acid. The A side and the B side may be mixed to form a curable composition. The method may include the step of curing the curable composition at a temperature of less than 50°C to form a reaction product. The method may include the step of mixing the first component and the second component to form a reaction product. The method may include a curing step, wherein the reaction product of the first component and the second component is cured at a temperature of less than 50°C. The method may be used with an A side comprising one or more epoxy resins, calcium carbonate, or both. The method may be used with a B side comprising one or more phosphate esters, phosphoric acid, or both. The method may be used with an A side, a B side, or both having one or more additives.

[0136] As used herein, unless otherwise stated, the teachings contemplate that any member of a genus (list) may be excluded from that genus; and / or any member of a Markush group may be excluded from that group.

[0137] Unless otherwise stated, the numerical values ​​described herein include all numerical values ​​from lower values ​​to higher values, with an increment of 1 unit, provided that there is at least an interval of 2 units between any lower value and any higher value. As an example, if the amount of the value of a component, characteristic or process variable (such as temperature, pressure, time, etc.) is stated to be, for example, from 1 to 90, preferably from 20 to 80, more preferably from 30 to 70, it is intended that the intermediate range values ​​(for example, 15 to 85, 22 to 68, 43 to 51, 30 to 32, etc.) are within the teaching of this specification. Similarly, separate intermediate values ​​are also within this teaching. For values ​​less than 1, a unit is considered to be 0.0001, 0.001, 0.01 or 0.1 as appropriate. These are only embodiments of specific intent, and all possible combinations of numerical values ​​between the lowest and highest values ​​listed should be considered to be the content clearly stated in a similar manner in this application. It can be seen that the teaching of the amount represented as "parts by weight" herein also contemplates the same range represented by weight percentage. Thus, language within a range of "at least "x" parts by weight" of a resulting composition also contemplates teaching of the same recited amount range of "x" percent by weight of the resulting composition.

[0138] Unless otherwise stated, all ranges include both endpoints and all numbers between the endpoints. The use of "about" or "approximately" in connection with a range applies to both ends of the range. Thus, "about 20 to 30" is intended to encompass "about 20 to about 30," including at least the specified endpoints. Unless otherwise stated, teachings with respect to the term "about" or "approximately" in combination with a numerical amount encompass teachings of the cited amount as well as approximate values ​​of the cited amount. For example, teachings of "about 100" encompass teachings of 100.

[0139] The disclosures of all articles and references, including patent applications and publications, are incorporated by reference for all purposes. The term "consisting essentially of" describing a combination shall include the identified elements, ingredients, components, or steps, as well as such other elements, ingredients, components, or steps that do not materially affect the basic and novel characteristics of the combination. The use of the terms "comprising" or "including" herein to describe a combination of elements, ingredients, components, or steps also contemplates embodiments consisting of or consisting essentially of the elements, ingredients, components, or steps.

[0140] Multiple elements, ingredients, components or steps can be provided by a single integrated element, ingredient, component or step. Alternatively, a single integrated element, ingredient, component or step can be divided into separate multiple elements, ingredients, components or steps. The disclosure of "a" or "one" describing an element, ingredient, component or step is not intended to exclude additional elements, ingredients, components or steps.

[0141] It should be understood that the above description is intended to be illustrative and not restrictive. Many embodiments and many applications other than the examples provided will be apparent to those skilled in the art after reading the above description. Therefore, the scope of the present invention should not be determined with reference to the above description, but with reference to the full scope of equivalents given by the attached claims and such claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. The omission of any aspect of the subject matter disclosed herein in the attached claims is not a waiver of rights to this subject matter, nor should it be considered that the inventor considers this subject matter to be a part of the disclosed inventive subject matter.

Claims

1. A curable adhesive formulation, comprising: Part A having one or more epoxy resins; a portion B having an acidic phosphorus-containing component; The binder comprises one or more of calcium carbonate, minerals, reinforcing fibers, hydrophobic silica, or any combination thereof.

2. A curable adhesive formulation, comprising: Part A having one or more epoxy resins; a portion B having an acidic phosphorus-containing component; Wherein the cured adhesive has a T-peel of at least about 2.5 N / mm as measured according to ASTM D1876.

3. The adhesive of claim 1 or 2, wherein the cured adhesive provides an assembly having a lap shear of at least about 15 MPa as measured according to EN2243-1.

4. The adhesive of any one of the preceding claims, wherein the acidic phosphorus-containing component comprises one or more phosphate esters, phosphoric acid, polyphosphoric acid, phosphorus pentoxide, or any combination thereof. 5 . The adhesive of claim 4 , wherein the one or more phosphate esters comprises a first phosphate ester, a second phosphate ester, a third phosphate ester, or any combination thereof.

6. The adhesive according to claim 4 or 5, wherein the one or more phosphate esters are independently the reaction product of phosphoric acid and: -alcohol; - epoxide groups of phosphate precursors (i.e., components that have not yet reacted with phosphoric acid); -monoepoxy functional molecules; - Glycidyl ether of cashew nut shell liquid (CNSL); -phenyl glycidyl ether; -2-ethylhexyl glycidyl ether; -Epoxidized p-tert-butylphenol.

7. The adhesive of any one of claims 4 to 6, wherein the one or more phosphate esters are present in an amount of about 0.1 wt % to about 30 wt % of the B-side; preferably about 10 wt % to about 14 wt % of the B-side.

8. The adhesive of any one of claims 4 to 6, wherein the at least one phosphate ester is present in an amount of about 10 wt % to about 60 wt % of the B side; preferably about 25 wt % to about 35 wt % of the B side; more preferably about 28 wt % to about 32 wt % of the B side.

9. The adhesive of any one of claims 4 to 6, wherein the at least one phosphate ester is present in an amount of about 5 wt % to about 40 wt % of the B side; preferably about 15 wt % to about 25 wt % of the B side; more preferably about 18 wt % to about 22 wt % of the B side.

10. The adhesive of any one of claims 4 to 6, wherein the at least one phosphate ester is present in an amount of about 10% to about 65% by weight of the B-side; preferably about 35% to about 45% by weight of the B-side.

11. The adhesive of any one of the preceding claims, wherein the part B comprises one or more non-phosphorus-containing acids or derivatives, one or more anhydrides, one or more additives, one or more monomers, or any combination thereof.

12. The adhesive of claim 11, wherein the one or more additives comprise minerals, reinforcing fibers, fumed silica, or any combination thereof.

13. The adhesive of any one of the preceding claims, wherein the adhesive comprises calcium carbonate.

14. An adhesive according to any preceding claim, wherein the adhesive comprises an elastomeric material.

15. The binder of any one of the preceding claims, wherein the binder comprises one or more of calcium carbonate, minerals, reinforcing fibers, hydrophobic silica, or any combination thereof.

16. A two-part system according to any one of the preceding claims, comprising calcium carbonate present in an amount of about 1 wt % to about 25 wt % of the Part A; preferably about 4 wt % to about 18 wt % of the A side; more preferably about 8 wt % to about 12 wt % of the A side.

17. An adhesive according to any preceding claim comprising a core-shell material.

18. An adhesive according to any preceding claim comprising hydrophobic silica.

19. An adhesive according to any preceding claim comprising platy aluminium oxide.

20. The adhesive of any of the preceding claims, wherein the one or more epoxy resins comprise one or more liquid epoxy resins, one or more flexible epoxy resins, one or more epoxy phenol novolac resins, one or more aliphatic multifunctional epoxy resins, one or more reactive diluents, one or more silane-modified epoxy resins, or any combination thereof.

21. The adhesive of any preceding claim, wherein the one or more epoxy resins comprise one or more liquid epoxy resins.

22. An adhesive according to claim 21, wherein the one or more liquid epoxy resins are independently the reaction product of epichlorohydrin and: a bisphenol; preferably bisphenol A, bisphenol F or both.

23. The adhesive of claim 21 or 22, wherein the one or more liquid epoxy resins have - an epoxy equivalent weight of about 100 g / equivalent to about 1000 g / equivalent as measured according to ASTM D1652-97; - an epoxy percentage of about 20 to about 25; and / or - A viscosity of about 10 cP to about 100,000 cP at 25°C as measured according to ASTM D445.

24. The adhesive of any one of claims 21 to 23, wherein the one or more liquid epoxy resins are present in an amount of about 4 wt % to about 50 wt % of the A side; the one or more liquid epoxy resins may be present in an amount of about 10 wt % to about 30 wt % of the A side; the one or more liquid epoxy resins may be present in an amount of about 8 wt % of the A side.

25. An adhesive according to any one of the preceding claims, wherein the one or more epoxy resins comprise one or more flexible epoxy resins; preferably independently selected from difunctional glycidyl ether epoxy resins, modified BPA-based epoxy resins, multifunctional epoxidized polybutadiene resins or any combination thereof.

26. The adhesive of claim 25, wherein the one or more flexible epoxy resins independently have - an epoxy equivalent weight of about 260 to about 500 as measured according to ASTM D1652-97; and / or - A viscosity of about 700 cP to about 500,000 cP at 25°C as measured according to ASTM D445.

27. An adhesive according to claim 25 or 26, wherein the one or more flexible epoxy resins are present in an amount of about 10 wt% to about 50 wt% of the A side; preferably about 35 wt% to about 45 wt% of the A side.

28. The adhesive of any one of claims 25 to 27, wherein the one or more flexible epoxy resins comprise - a difunctional glycidyl ether epoxy resin in an amount of about 10% to about 18% by weight of the A side, - an unmodified BPA-based epoxy resin in an amount of about 8% to about 16% by weight of the A side, - a multifunctional epoxidized polybutadiene resin in an amount of about 8% to about 16% by weight of the A side.

29. The adhesive of any one of the preceding claims, wherein the one or more epoxy resins comprise one or more epoxy phenol novolac resins.

30. The adhesive of claim 29, wherein the one or more epoxy phenol novolac resins have - an epoxy equivalent weight of about 165 g / equivalent to about 183 g / equivalent as measured according to ASTM D1652-97; - an average epoxy functionality of from about 2.1 to about 6.5; and / or - A viscosity of about 18,000 cP to about 30,000 cP at 25°C as measured according to ASTM D445.

31. An adhesive according to claim 29 or 30, wherein the one or more epoxy phenol novolac resins are present in an amount of about 30 wt % to about 50 wt % of the A side; preferably about 35 wt % to about 45 wt % of the first component or A side; more preferably about 38 wt % to about 42 wt % of the A side.

32. The adhesive of any one of claims 29 to 31, wherein the one or more epoxy phenol novolac resins comprise - an about 3.6 functional epoxy phenol novolac resin present in an amount of about 2 wt % to about 18 wt % of the A side and an about 6.5 functional epoxy novolac resin present in an amount of about 22 wt % to about 32 wt % of the A side; - about 3.6 functional epoxy phenol novolac resin present in an amount of about 15 wt % of the A side and about 6.5 functional epoxy novolac resin present in an amount of about 28 wt % of the A side; and / or - About 3.6 functional epoxy phenol novolac resin and about 6.5 functional epoxy phenol novolac resin in a ratio of about 1:2 to about 1:

3.

33. An adhesive according to any preceding claim, wherein the one or more epoxy resins comprise one or more aliphatic multifunctional epoxy resins; preferably epoxidized sorbitol.

34. The adhesive of claim 33, wherein the one or more aliphatic multifunctional epoxy resins have - an epoxy equivalent weight of about 160 g / equivalent to about 195 g / equivalent as measured according to ASTM D1652-97; and / or - A viscosity of about 200 cP to about 18,000 cP at 25°C as measured according to ASTM D445.

35. An adhesive according to claim 33 or 34, wherein the one or more aliphatic multifunctional epoxy resins are present in an amount of about 5 wt % to about 20 wt % of the A side; preferably 8 wt % to about 16 wt % of the A side; more preferably about 10 wt % to about 14 wt % of the A side.

36. An adhesive according to any one of the preceding claims, wherein the one or more epoxy resins comprises cashew nut shell liquid; preferably a glycidyl ether of cashew nut shell liquid; more preferably a glycidyl ether of cardanol.

37. An adhesive according to any preceding claim, wherein the one or more epoxy resins comprise one or more reactive diluents; preferably polyethylene glycol diglycidyl ether, trimethylolethane triglycidyl ether or both.

38. An adhesive according to claim 37, wherein the one or more reactive diluents are present in an amount of about 5 wt % to about 20 wt % of the A side; preferably about 8 wt % to about 16 wt % of the A side; more preferably about 10 wt % to about 14 wt % of the A side.

39. The adhesive of any preceding claim, wherein the one or more epoxy resins comprise one or more epoxy-functional silanes or silane-modified epoxy resins.

40. The adhesive of claim 39, wherein the one or more silane-modified epoxy resins are present in an amount of about 1 wt % to about 15 wt % of the A side; preferably about 2 wt % to about 6 wt % of the A side; more preferably about 4 wt % of the A side.

41. The adhesive of any preceding claim comprising one or more liquid epoxy resins comprising the reaction product of epichlorohydrin and bisphenol A.

42. The adhesive of any preceding claim, wherein the cured adhesive has a tensile modulus of at least 1000 MPa as measured according to ISO 527.

43. An adhesive according to any preceding claim wherein the part A comprises epoxidised linseed oil.

44. The adhesive of any preceding claim wherein any components in Part B are not physically separated from the acidic phosphorus-containing ingredient.

45. An adhesive according to any preceding claim, wherein Part A and Part B are substantially free of any fibrous material.

46. ​​The adhesive of any preceding claim, wherein the epoxy resin comprises an aliphatic epoxy resin.

47. An adhesive according to any preceding claim, wherein part A comprises epoxidised linseed oil in an amount greater than 0.5% but less than 10%.

48. An adhesive according to any preceding claim, wherein part A comprises epoxidised linseed oil in an amount greater than 1% but less than 6%.

49. The adhesive of any preceding claim, wherein part A comprises bisphenol A epoxy resin in an amount of at least 0.5%.

50. The adhesive of any preceding claim, wherein part A comprises bisphenol A epoxy resin in an amount of at least 2.5%.

51. The adhesive of any one of the preceding claims, wherein Part A comprises bisphenol A epoxy resin and epoxidized linseed oil in a ratio of about 1 part bisphenol A epoxy resin: 2 parts epoxidized linseed oil to about 2 parts bisphenol A epoxy resin: about 1 part epoxidized linseed oil.

52. The adhesive of any one of the preceding claims, wherein Part A comprises bisphenol A epoxy resin and epoxidized linseed oil in a ratio of about 1 part bisphenol A epoxy resin: 1 part epoxidized linseed oil.

53. The adhesive of any one of the preceding claims, wherein Part A comprises a difunctional glycidyl ether epoxy resin and epoxidized linseed oil in a ratio of about 3 parts difunctional glycidyl ether epoxy resin to about 1 part epoxidized linseed oil.

54. The adhesive of any one of the preceding claims, wherein the Part A and the Part B are present in a ratio of about 4 parts Part A to about 1 part Part B.

55. The adhesive of any one of the preceding claims, wherein the adhesive cures at room temperature (about 20°C to about 23°C).

56. The adhesive of any preceding claim, wherein the speed at which the adhesive cures can be increased with the addition of heat.

57. A method of adhering a first substrate to a second substrate, the method comprising positioning the adhesive of any one of the preceding claims on the first substrate and positioning the second substrate in contact with the adhesive within 5 minutes.

58. The method of claim 57, wherein Part A of the adhesive mixes with Part B of the adhesive within 5 minutes of positioning the adhesive on the first substrate.

59. An adhesive formulation, comprising: Part A having epoxy resin; a portion B having an acidic phosphorus-containing component; Wherein the cured adhesive has a T-peel of at least about 2.5 N / mm as measured according to ASTM D1876.

Citation Information

Patent Citations

  • Foamed articles and methods for making same

    US5648401A

  • Creation of epoxy-based foam-in-place material using encapsulated metal carbonate

    US6730713B2

  • Esterified acids for use in polymeric materials

    WO2016149700A1